Predictive Role of Sexual Self-concept in Marital Satisfaction and Sexual Function in Reproductive-aged Women - Robabeh Potki; Tayebe Ziaei; Mahmood Moosazadeh; Mahbobeh Faramarzi; Zohreh Shahhosseini (Mashhad University of Medical Sciences, 2020)
Background & aim: Sexual self-concept is a cognitive perspective of humans towards their sexual aspects, which reflects their thoughts, feelings, and functions about themselves as sexual creatures and could be a predictor of sexual outcomes. This study aimed to investigate the predictive role of sexual self-concept about marital satisfaction and sexual function in reproductive-aged women. Methods: This correlational study was conducted on 707 married women (aged 15-49 years) in Sari, North of Iran, in 2016. The subjects were selected by systematic sampling. The data were collected using Snell Multidimensional Sexual Self-concept Questionnaire, ENRICH Marital Satisfaction Scale, and Rosen Female Sexual Function Index. Data analysis was performed using Pearson correlation coefficient, independent t-test, ANOVA, and linear regression tests in SPSS software (version 16.0). Results: The positive domain of sexual self-concept had the maximum mean score (130.38±19.71). In this domain, the maximum score belonged to motivation to avoid risky sex. The negative domain of sexual self-concept (9.10±9.16) had the minimum score, with sexual monitoring having the maximum score. The results of the linear regression model showed that sexual self-concept could predict 43% and 36% variances of marital satisfaction and female sexual function, respectively. Conclusion: This study facilitates the conceptualization of sexual health issues. Based on the findings, it is recommended to pay attention to the transactional correlation of sexual self-concept with marital satisfaction and sexual function in primary healthcare settings.